Association Between Staphylococcal Enterotoxin-Specific IgE and House-Dust-Mite-Specific IgE in Brazilian Patients with Chronic Rhinosinusitis with Nasal Polyps - Priscilla Campos; Sérgio Duarte Dortas Junior; Solange Oliveira Rodrigues Valle; Nathalia Novello Ferreira; Fabiana Chagas da Cruz; Priscila Novaes Ferraiolo; José Elabras Filho (Sinusitis, 2025)
Chronic Rhinosinusitis (CR) is a common inflammatory condition with complex pathophysiology involving multiple interleukins. In times of precision medicine, it is mandatory to cluster our patients to offer the best tailored treatment with the lowest cost possible. Therefore, some triage markers can be used towards this goal, without raising much financial burden. The aim of this study was to identify the association of staphylococcal enterotoxin (SE)-specific IgE of types A, B, C, and TSST-1 (toxic shock syndrome toxin-1); and total IgE (tIgE) and specific IgE for Dermatophagoides pteronyssinus (DP), Dermatophagoides farinae (DF), and Blomia tropicalis (BT) in Brazilian patients with CRSwNP. Thirty-six patients with CSRwNP were analyzed for serum IgE levels: tIgE and specific IgE for: DP, DF, BT, and SE types A, B, C, TSST-1 by ImmunoCAP®. The mean value of tIgE in SE-specific IgE-positive patients was 767 IU/mL and in house-dust-mite (HDM)-positive patients, the mean tIgE was 319 IU/mL (p < 0.005). A total of 86% of patients who had high tIgE levels but were SE-specific IgE-negative had positive specific IgE for at least one of the HDMs tested. The Fisher exact test statistic value for this association was significant (p < 0.05/p = 0.014). We found an association between high levels of tIgE and SE-specific IgE in patients with CRSwNP, possibly related to local and peripheric polyclonal IgE production. The mean value of tIgE—with a suggested cutoff point of tIgE levels of 767 IU/mL—can be used as a triage biomarker for positive SE-specific IgE in CRSwNP patients.